Educational Values in Fathul Kutub: The Experience of Students of Pondok Modern Darussalam Gontor - Fanisa Aulia Putri; Fairuz Subakir (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This article aims to analyze and describe the educational values contained in Fathul Kutub's activities based on the experiences of KMI final grade students at Pondok Modern Darussalam Gontor For Girls Campus 3. The study employed a descriptive qualitative method with a case study approach. Data were collected in-depth interviews, direct observation during the activity, and documentation, including field notes and Fathul Kutub assignment sheets. The findings indicate that Fathul Kutub activities do not only function as a means of strengthening student’s academic and linguistic competence, but also serve as a strategic medium from internalizing educational values. These values include independence, discipline, cooperation and mutual respect, self-confidence, responsibility, critical thinking, respect for different opinions. In terms of Arabic language development, Fathul Kutub contributes to improving students four language skills, namely listening, speaking, reading, and writing, through direct engagement with classical Islamic texts. The internalization of this value occurs through an experiential learning process in which students actively search, analizy, discuss and present ideas based on authoritative references. These findings imply that Pesantren educators need to design contextual, text-based learning activities that strengthen both students’ intellectual capacity and character formation in the digital era will facing contemporary educational challenges more effectively.